The Meaning and Implementation of Muṣāfaḥah in Islamic Social Interaction: A Moral and Sharia Perspective - Abdul Shomad; Ahmad Basuni; Suhendi, Suhendi (Penerbit Hellow Pustaka, 2026)
Social interaction is a crucial aspect of human life and plays a strategic role in building harmonious, compassionate, and dignified relationships. From an Islamic perspective, social interaction must be based on faith, morals, and sharia, and reflect brotherhood and moral values. One recommended form of interaction is shaking hands (muṣāfaḥah), which not only serves as a symbol of respect and affection but also has a spiritual dimension in strengthening brotherhood. This study aims to analyze the meaning, purpose, and implementation of the practice of muṣāfaḥah in Islamic social interaction, including the differing views of Islamic scholars regarding the ruling on shaking hands between members of the opposite sex and its implications for the formation of morality, discipline, and respect in students. The method used was qualitative research with a library research approach. Data were obtained from the Quran, hadith, classical and contemporary fiqh books, as well as previous research and related academic literature. The analysis was conducted descriptively thematically with data reduction, narrative presentation, and conclusion drawing, and validated through source triangulation. The results of the study indicate that muṣāfaḥah plays an important role in fostering brotherhood, compassion, and eliminating negative prejudice. From a legal perspective, the Shafi'i school of thought prohibits shaking hands between men and women who are not mahram unless a barrier is used, while the Hanbali school of thought considers this practice makrooh (disliked) with certain exceptions. Practical implementation emphasizes the sharia context and the principle of caution so that muṣāfaḥah can be a means of strengthening brotherhood, maintaining honor, and fostering social morals in accordance with Islamic principles. This study provides theoretical and practical contributions to Islamic education in formulating guidelines for safe, dignified social interactions that are relevant to the needs of contemporary learners.